PENGEMBANGAN INSTRUMEN PENILAIAN DIRI PADA MATA PELAJARAN BAHASA INDONESIA KELAS VI SD INDRIASANA PALEMBANG - Agnes Tri Sundari (Universitas Katolik Musi Charitas, 2019)
This research is entitled The Development of Self Assessment in Indonesian Language Lessons in Class VI of SD Indriasana Palembang. This research was motivated by the absence of self-assessment instruments on Indonesian language subjects for grade VI elementary school students, especially SD Indriasana Palembang. The purpose of this study was to produce new products for self-assessment instruments of grade 6 students of SD Indriasana Palembang. This study developed an attitude assessment instrument based on KI 2 in KD 2.1, which has responsibility for the characteristics of living things and the environment through the use of Indonesian. This research is a type of Strategy and Development (R & D). From the 10 stages of Borg and Gall, researchers only reached 3 stages, namely: needs analysis, initial product development, and validation. Data collection is done by interview techniques and questionnaires. The results of the study were in the form of a class VI self assessment instrument needed at SD Indriasana Palembang. The results of the study also state that self-assessment instruments can be included in the valid category and can be used with revisions.